If I were a rich man could I sell a pancreas? A study in the locus of oppression. Issue 2 (20th October 2010) - Epstein, M
Abstract : Dan Brock argues that since the unexploitable rich could sell their kidneys too, exploitation could not be an essential feature of organ vending. This paper takes his claim as the point of departure for a discussion on the locus of organ vending-associated oppression. While it accepts Brock's conclusion, it explores the possibility that such oppression is invariably found rather outside the sphere of exchange. It then analyses the implications of this possibility for the discourse surrounding the ethics of organ vending.